ANALISIS UNSUR INTRINSIK NOVEL SUWUNG: TENTANG MANUSIA YANG BERUMAH DI DALAM MIMPI KARYA HENDRA PURNAMA - Haeniah, Nurul; Ketut Tia Apriliani (Journal of Language and Literature Education, 2024)
This study aims to uncover the intrinsic elements in the novel "Suwung: Tentang Manusia Yang Berumah Di Dalam Mimpi" by Hendra Purnama. The method employed is descriptive qualitative. The data used in this study consists of quotes and paragraphs based on their intrinsic elements. These data are sourced from the novel "Suwung" by Hendra Purnama, which are then analyzed using various theories relevant to the research topic. The findings of this study include: (1) Theme: Exploration of emptiness, void, loneliness, loss, and love. (2) Plot: The use of a mixed plot combining both forward and backward sequences. (3) Setting: A variety of settings including home, cafe, cemetery, and hospital, with times of day ranging from morning, afternoon, evening, to night, and atmospheres encompassing sadness, tension, and happiness. (4) Characters and Characterization: In-depth characterization of the main character Indra Pratama, and supporting characters such as Irwan Rahardian, Airin Rahimi, and Afriani Zakiah. (5) Point of View: A combination of first-person and third-person perspectives providing diverse viewpoints. (6) Language Style: The use of hyperbolic language and similes enriching the narrative. (7) Moral Message: A strong message about perseverance and the importance of self-love in life. This study provides valuable contributions to literary studies, particularly in understanding Hendra Purnama's work, through an in-depth and comprehensive analysis of the intrinsic elements in the novel "Suwung". Keywords: instrinsic elements, novel